CONTEXTUALIZATION OF HADITH REGARDING THE PROHIBITION OF ANNOUNCING LOSS IN THE MOSQUE (A Study of the Meaning of Hadith) - Bachtiar, Fatchur Yunan; Darmawan, Herman; Hasbi, Anang Fajar; Fitri, Muhammad; Jikri, Muhammad (RIWAYAH, 2024)
As an identity of the Islamic community, the mosque holds a very important role and function. The mosque does not only focus on activities related to the afterlife but integrates both spiritual (ukhrawi) and worldly (duniawi) activities. Regarding the function of the mosque, the Prophet Muhammad (peace be upon him) prohibited the announcement of lost items in the mosque because it was not built for such a purpose. However, this prohibition contrasts with the mosque’s function not only as a place of worship but also as a medium to address social issues within the community. Therefore, this study aims to understand the hadith related to this prohibition by examining its contextualization in the study of Ma’anil Hadith. This research is a library study using qualitative methods, conducted by collecting and analyzing data relevant to the issue being investigated. The results of this study are: First, the hadith prohibiting the announcement of lost items in the mosque signifies that the mosque is a sacred place, with a peaceful and calm atmosphere, where worship activities such as prayer are performed. Second, when contextualized in the present day, there are many ways to search for lost items in the mosque, such as reporting the loss to the mosque administrators, asking the congregation at the mosque doors, looking in the lost and found area outside the mosque, and posting announcements about lost items on the information board outside the mosque. [Sebagai identitas komunitas Islam, masjid memegang peran dan fungsi yang sangat penting. Masjid tidak hanya fokus pada kegiatan yang berkaitan dengan kehidupan akhirat tetapi juga mengintegrasikan kegiatan spiritual (ukhrawi) dan duniawi (duniawi). Mengenai fungsi masjid, Nabi Muhammad melarang pengumuman barang yang hilang di masjid karena masjid tidak dibangun untuk tujuan tersebut. Namun, larangan ini bertentangan dengan fungsi masjid yang tidak hanya sebagai tempat ibadah tetapi juga sebagai media untuk menangani masalah sosial dalam komunitas. Oleh karena itu, penelitian ini bertujuan untuk memahami hadis yang terkait dengan larangan ini dengan menelaah kontekstualisasinya dalam studi Ma’anil Hadith. Penelitian ini adalah studi pustaka yang menggunakan metode kualitatif, dilakukan dengan mengumpulkan dan menganalisis data yang relevan dengan isu yang sedang diselidiki. Hasil dari penelitian ini adalah: Pertama, hadis yang melarang pengumuman barang hilang di masjid menandakan bahwa masjid adalah tempat yang suci, dengan suasana yang damai dan tenang, tempat di mana kegiatan ibadah seperti salat dilakukan. Kedua, ketika dikontekstualisasikan pada masa sekarang, ada banyak cara untuk mencari barang yang hilang di masjid, seperti melaporkan kehilangan kepada pengelola masjid, bertanya kepada jamaah di pintu masjid, mencari di area barang hilang di luar masjid, dan memposting pengumuman tentang barang hilang di papan informasi di luar masjid].